The Determinants Of Corporate Value In The Indonesia Sharia Stock Index (ISSI) - Faisal, Agus; Nissa, Izzun Khoirun (International Journal of Islamic Business and Economics (IJIBEC), 2018)
In the current era of business competition is getting tighter, strategies to get customer loyalty need to be increased. Because with such an effort to increase the value of the company. This paper aims to examine the effect of profitability (ROA), Liquidity (CR) and debt policy (DAR) on the value of the company in the Indonesian Sharia Stock Index (ISSI). This research is anstudy explanative with a duration of four years from 2012-2015, in the ISSI index there are 100 samples taken by purposive sampling technique.  Data analysis using panel data analysis techniques with Eviews 8 software applications. The results of the study show that simultaneously profitability, liquidity, and debt policy affect the value of the company.